Research on the impact of the integration of digital economy and real economy on China’s domestic value chain resilience - Chunhui Huo; Shengkai Bian; Di He; Mengxiao Lv (Digital Economy and Sustainable Development)
Abstract Purpose The integration of the digital economy and the real economy plays a pivotal role in building a high-level, self-reliant, and robust national economic circulation system. Drawing on theories of intra-product specialization and industrial linkage, this study innovatively explores the impact of digital-real economy integration on the resilience of domestic value chains from the perspective of stabilizing and strengthening these chains. Methods This study adopts the classification standards for core digital industries outlined in the Statistical Classification of the Digital Economy and Its Core Industries (2021) issued by the National Bureau of Statistics of China, aligning them with the industries in China’s interprovincial input–output tables for 2012, 2015, and 2017. The analysis employs the Gradient Boosting algorithm within a double machine learning framework. Results The findings reveal that digital-real integration significantly enhances the resilience of domestic value chains, with a one-standard-deviation increase in integration reducing the volatility of value chain length by 4.22%. Further analysis indicates that the integration more effectively bolsters value chain resilience in regions with higher total factor productivity and greater market integration. Moreover, high-quality regional development and the establishment of a unified national market contribute to strengthening the central position of domestic value chains. Additionally, digital-real economy integration facilitates the connection between domestic and international markets, enabling inland regions to participate more deeply in global value chain specialization. Conclusions These conclusions underscore the necessity of developing and innovating digital-real economy integration policies centered on stabilizing and strengthening value chains, thereby enhancing the intrinsic dynamism and reliability of domestic value chains.